305 CHYLOTHORAX IN AN INFANT WITH FEATURES OF PETERS PLUS SYNDROME. Issue 1 (1st January 2007) - Aubertin, G. M.; McFadden, D. E.; Lyons, C.; Sandor, G. G.; Hurley, R. M.; Yong, S. L.
Abstract : Peters Plus syndrome is a rare autosomal recessive condition associated with anterior eye chamber anomalies, disproportionate short stature, and developmental delay. There are characteristic facial features and increased rates of cardiac and renal malformations. We describe a case of a premature male infant with clinical features of Peters Plus syndrome, born to nonconsanguinous parents. There were prenatally detected bilateral nonimmune chylothoraces and ascites of unknown etiology. Postnatal findings included an anterior chamber defect of the right eye, bilateral preauricular ear pits, short midface, anteverted nares, prominent cupid's bow of the upper lip, and a single umbilical artery. Echocardiography identified an enlarged right atrium and ventricle, a large patent ductus arteriosus, atrial septal defect, and poor global cardiac function. Bilateral cystic dysplastic kidneys were seen on a sonogram at birth. The course was complicated by pulmonary hypertension, respiratory failure requiring continuous ventilator support, impaired renal function, and persistent hydrops. The infant died at a corrected gestational age of 40 weeks from kidney and cardiac failure. Postmortem autopsy revealed extensive subendocardial right ventricular calcification, focal glomerulocystic changes of the kidneys, and disproportionately short limb measurements. Karyotyping and subtelomeric fluorescence in situ hybridization (FISH) were normal. A family history of Wilms' tumor prompted FISH analysis for PAX6 and WT1 with no evidence of microdeletion. Chylothorax has not previously been described in association with Peters Plus syndrome and may represent an additional clinical manifestation.